A Challenge for the Next Decade: Preserving Affordable Rental Housing - Burns, Laura (Maine Policy Review, 1999)
Many of Maine’s low-income families and elderly residents have been able to secure affordable housing with help from a Section 8 certificate, which allows residents to pay no more than 30 percent of their income toward rent and ensures the federal government will make up the difference. Over the years, much of the development of Section 8 housing projects has been assisted by financial incentives and agreements between private and non-profit owners and the federal government. Yet recent changes in federal legislation remove many of these incentives and the agreements that go with them. As a result, some of Maine’s affordable housing supply may disappear as private owners convert their properties to market-rate rental housing. Laura Burns outlines the recent changes in federal legislation and discusses their potential impact on Maine’s communities. Currently in Maine, there are 3,500 assisted rental apartments with Section 8 contracts scheduled to expire in the next five years. Without any incentives to renew, the owners of these projects face the economic decision of whether to continue to provide affordable housing without any of the incentives or guarantees that previously existed, or to convert their properties to market rate. Burns argues that local and state officials must do what they can now to keep the state’s already scarce supply of affordable housing in place.